2020
DOI: 10.1111/gcb.14949
|View full text |Cite
|
Sign up to set email alerts
|

Halving sunlight reveals no carbon limitation of aboveground biomass production in alpine grassland

Abstract: In temperate alpine environments, the short growing season, low temperature and a slow nutrient cycle may restrict plant growth more than carbon (C) assimilation does. To test whether C is a limiting resource, we applied a shade gradient from ambient light to 44% (maximum shade) of incident photon flux density (PFD) in late successional, Carex curvula‐dominated alpine grassland at 2,580 m elevation in the Swiss central Alps for 3 years (2014–2016). Total aboveground biomass did not significantly decrease under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…Beside its signalling effect, a short photoperiod also encompasses lower levels of photon fluxes, possibly limiting carbon uptake. However, perennial alpine plants have large belowground reserves 33 and are not carbon-limited 34 , even under shade 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside its signalling effect, a short photoperiod also encompasses lower levels of photon fluxes, possibly limiting carbon uptake. However, perennial alpine plants have large belowground reserves 33 and are not carbon-limited 34 , even under shade 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The sedge Carex curvula (Fig. 1B) is the dominant species, contributing around one third to total annual biomass production 35,59 . Grasses like Helictotrichon versicolor Vill.…”
Section: Vegetationmentioning
confidence: 99%
“…Our seasonal harvests under common alpine life conditions revealed little influence of aboveground growth -irrespective of the plant stature- on NSC concentrations in the belowground organs, so, NSC storage has an overwhelming priority for these alpine plants. Moreover, CO 2 enrichment and shading experiments in situ revealed that carbon is not a limiting resource for alpine plants (Körner et al 1997 ; Inauen et al 2012 ; Möhl et al 2020 ) and tall alpine forbs are no exception in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Young trees with a smaller canopy also have a smaller rooting zone, less litter fall and nutrient cycling, less contribution to water redistribution and so forth. What is more, the artificial shade constructions are expected to have altered aboveground microclimatic conditions such as changes in precipitation distribution, canopy temperature, wind speed and evaporative force (Friday & Fownes, 2002; Möhl et al, 2020; Siemannand Rogers, 2003). Nonetheless, field experiments that approximate natural conditions as closely as possible while meeting the scientific requirements of controlled, replicable experimental conditions are of high informative value (Sollen‐Norrlin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%